Xerostomia, fluxo salivar e sua correlação com adaptação às próteses totais - Chiquito, Tamires Matos Felix [UNESP] (2017)
The elderly population presents several oral alterations, specially the decrease of the salivary flow, which can hinder the adaptation to the complete dentures. This study aimed at quantifying the salivary flow and evaluating the presence of xerostomia in complete dentures users and correlating these data with how long the patients adapt to the new conventional complete dentures. Forty volunteers who attended the Total Prosthesis Clinic of Paulista State University Júlio de Mesquita Filho UNESP, Araçatuba-SP, Brazil, were invited to respond to a questionnaire containing information on the presence or absence of xerostomia. The questionnaire was submitted to sialometry tests and to an analysis of the predominant salivary type. The study was divided in two phases: questionnaire and evaluation of salivary flow that was performed through sialometries, in two stages: 1st stage - immediately after the installing process of the complete dentures and 2nd stage - four months after the installation of the complete dentures. In the first stage, the sialometry was performed in three different moments, with weekly intervals between the collections. In the second stage, a single collection of saliva plus an evaluation of the prostheses and, when necessary, adjustments for better adaptation were performed. In addition, guidelines on oral hygiene and care of the new complete dentures have been strengthened at this time. The data were submitted to statistical tests, at the significance level of 5%. Relating the salivary flow to the three collection phases, xerostomia or predominant saliva type, there was no statistical difference (p> 0.05). In the second stage (4th collection), correlating salivary flow with xerostomia, there was a statistical difference (p <0.05). It was concluded that the saliva type and gender did not interfere in the presence of xerostomia, and that...